Study on the safety and excellent probiotic properties of fermentation strains isolated from traditional dry-cured duck for starter development. (February 2023) - Li, Xiao-min; Deng, Jie-ying; Nie, Wen; Li, Cong; Xu, Bao-cai
Abstract: The indigenous starter cultures isolated from fermented food can compete with spoilage and pathogenic bacteria and improve the flavor and organoleptic properties of products. The purposes of this work were to screen and assess the safety, potential probiotic, and fermentation properties of indigenous starter cultures isolated from dry-cured ducks. The properties of indigenous starter cultures were investigated by antibiotic resistance, virulence genes, in vivo toxicity, simulated gastrointestinal, adhesion capacity to Caco-2 cells, inoculation fermentation, etc. Overall, six strains were isolated and identified, including Lactobacillus sakei D15, Weissella hellenica D20, Lactobacillus curvatus D2, Staphylococcus simulans D12, Staphylococcus equorum D19, and Staphylococcus edaphicus D17. The obtained strains showed high safety. Additionally, most strains displayed excellent probiotic properties, including tolerance to lower pH, lysozyme, bile salt, and a high survival rate of the simulated gastrointestinal phase. The adhesion ability of strain cells to Caco-2 cells was 9.22%–14.21%. And the probiotic properties of strains can be strengthened by the expression of specific enzymes. The inoculation with the isolated strains (LS-D15, LC-D2 and SS-D12) could contribute to the formation of volatile flavor compounds in samples. Overall, results demonstrated that strains possessed excellent safety and probiotic properties, and can be used as starter cultures to enhance the quality and flavor of the dry-cured duck. Graphical abstract: Image 1 Highlights: The indigenous starter cultures were selected from dry-cured duck. Most of strains possessed good safety and showed low toxic effect. Additionally, the isolated strains showed excellent probiotic properties. Inoculation with the isolated strains promoted the formation of VFCs of samples. The strains are suitable as starter culture in the manufacture of dry-cured duck.